2023
DOI: 10.3390/cryst13010137
|View full text |Cite
|
Sign up to set email alerts
|

Experiments and Crystal Plasticity Finite Element Simulations of Texture Development during Cold Rolling in a Ti-15V-3Cr-3Sn-3Al Alloy

Abstract: The effect of deformation on the evolution of crystallographic texture in a Ti-15V-3Cr-3Sn-3Al (Ti-15333) alloy after unidirectional cold rolling was studied experimentally and numerically in the present investigation. An optical microscope (OM) and scanning electron microscope (SEM) were used to study the microstructures, while the crystallographic texture after cold rolling was studied with X-ray diffraction. The rolling process (deformation) was simulated with PRISMS-plasticity, open-source crystal plastici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The low-strain-rate deformation of metallic materials often involves mechanisms of slip and twinning deformation. Dislocation slip bands were observed at low strain rates when deforming β-Ti alloys [48,49]. During the tensile loading of two-phase Ti alloy [50], it was found that fracture was initiated at GBs, and GB sliding through dislocation slip was responsible for intergranular cracks at slow strain rates.…”
Section: Deformed Microstructure and Texture Evolutionmentioning
confidence: 98%
See 2 more Smart Citations
“…The low-strain-rate deformation of metallic materials often involves mechanisms of slip and twinning deformation. Dislocation slip bands were observed at low strain rates when deforming β-Ti alloys [48,49]. During the tensile loading of two-phase Ti alloy [50], it was found that fracture was initiated at GBs, and GB sliding through dislocation slip was responsible for intergranular cracks at slow strain rates.…”
Section: Deformed Microstructure and Texture Evolutionmentioning
confidence: 98%
“…β-Ti alloys also slip on planes other than {110} in the <111> direction, such as {112}<111> and {123}<111>. Severe deformation may activate additional deformation modes, such as SIM, mechanical twins, and SBs in deformed β-Ti alloys [48]. It is important to note that, similar to stacking fault energy in FCC alloys, β-phase stability can act as a criterion for the deformation mode in BCC β-Ti alloys.…”
Section: Slip and Twin Deformation In β-Ti Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the texture growth was more strongly reliant on the strain path than the original microstructure during cold rolling. Mahadule et al [7] analyzed the texture development during cold rolling in a Ti-15V-3Cr-3Sn-3Al alloy via experiments and numerical modeling based on crystal plasticity. It was observed that γ-(normal direction, ND//<111>) and α-(rolling direction, RD//<110>) fibers strengthened with cold rolling.…”
Section: Introductionmentioning
confidence: 99%
“…Chen [ 12 ] studied the evolution of the microstructure and properties of magnesium-alloy plates during ZK61 magnesium-alloy rolling. Texture evolution depends on rolling parameters (reduction, temperature) and deformation [ 13 , 14 ]. Accordingly, the influence of texture of ZK61 magnesium alloy in rolling state on the microstructure and properties of plate rolling is particularly important.…”
Section: Introductionmentioning
confidence: 99%